ANALISIS PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK: LITERATURE REVIEW - Dini Agustin; Yosi Gumala (PT Innovative Academic Journals, 2025)
This research aims to explore the application of the Snowball Throwing learning model and its influence on improving student learning outcomes through a literature review. Snowball Throwing is a learning model that involves students' active participation in the learning process in a fun and creative way through discussion. This model has proven successful in increasing student participation and learning outcomes because it encourages them to actively interact and work together in solving problems. This research uses a literature review method, by collecting data from various journal sources, articles and related research. The results of the analysis show that consistently applying the Snowball Throwing model can improve student learning outcomes, especially in terms of understanding concepts, critical thinking skills, and collaboration between students. This research suggests that the Snowball Throwing model be applied as an effective learning method, especially in learning contexts that prioritize active interaction. It is hoped that these findings can help educators in choosing appropriate learning methods to support improved learning outcomes.